DETERMINATION OF PURCHASE AND REPURCHASE DECISIONS: PRODUCT QUALITY AND PRICE ANALYSIS (CASE STUDY ON SAMSUNG SMARTPHONE CONSUMERS IN THE CITY OF JAKARTA) - Fauzi, Dandy Hafidh Fauzi; Ali, Hapzi (Dinasti Publisher, 2021)
This study aims to analyze the effect of Product Quality and Price on Purchase Decisions and their impact on Repurchase on Samsung smartphone consumers in the city of Jakarta. The population in this study are consumers who have purchased and used Samsung smartphone products located in the city of Jakarta. The number of samples used is based on the number of indicators multiplied by 5 to obtain 180 respondents. The research data was obtained through a survey conducted using a questionnaire and data analysis using Partial Least Square (PLS) version 3.0. The results showed that product quality and price had a positive and significant effect on purchasing decisions, product quality had no effect on repurchases, prices had a positive and significant effect on repurchases, and purchase decisions were not able to mediate the relationship between product quality and repurchase, but were able to mediate relationship between Price and Repurchase.